Business Plan-XiaoMiShu - WU, LIHUI (2019)
XiaoMiShu is an app which will be dedicated to help all international Chinese students to live better in a foreign country. Automatic intelligent information recommendation based on international Chinese students will save their time. Rightful partner matching will help them find the partner who has the same interests and preferences. Online second-hand goods selling platform will not only help students sell their goods, but also help accommodation agents save resources to reduce tons of general waste when students leave. On the other hand, it will also become a platform for British SMEs to connect with their customers and promote their products or service.